Popular Sovereignty in Political Thought of WEST and Islam; “Democratic System” and “Shari’a Based System in Iranian Constitution” - alireza dabirnia; Tayebe Asadabadi (پژوهش تطبیقی حقوق اسلام و غرب, 2016)
Popular sovereignty in western political thought, which manifests in a democratic system, begins by identifying the individual as an end. In this school of thought, on one hand, a person has a separate individuality from society and government and is able to provide his or her own definition about the relation between man and universe. Accordingly, the concept of popular sovereignty is intertwined with government representative and in a social contract, people establish the principles of constitution and legitimacy of laws and government are considered as the result of their will and consent. Thus, the most important function of government is to be bound to the representation and guarantee the people’s rights and liberties. A direct relationship can be observed between popular sovereignty and divine sovereignty in religious principles of Iran’s constitution. On one hand, divine sovereignty, is considered as vesting the self- determination right to people by God, as a divine right. On the other hand, people have defined their own destiny within Islamic religious principles, by freely acceptance of sacred principles. So, there is no confliction between religious principles and popular sovereignty, but disputes on sovereignty principles will arises from two different perspectives.